Antecedents and consequences of destination choice among tourists in Langkawi, Malaysia - Ismail, An Nur Nabila (2021)
Langkawi Island is considered one of the top tourism destinations in South East Asia. However, there are still many factors that can contribute to its competitiveness in the tourism industry. The study highlights the pull and push factor which includes travel motivation and destination personality as the drive that can influence holidaymakers in deciding holiday destinations. As information is considered crucial to tourists in choosing a holiday destination, the study also explores the marketing effort by examining the elements of electronic word of mouth and content marketing as sources for tourists to have an idea about the destination before they choose it. Langkawi is well known as a UNESCO Geopark, thus, environmental sustainability has become an essential issue and is explored in the study, as well as tourist satisfaction and intention to revisit. With the support of the Expectation Disconfirmation Theory (EDT) and Stimulus-Organism-Response Model (SOR), the research aims to examine the relationship between travel motivation (TM), destination personality (DP), electronic word of mouth (e-WOM), and content marketing (CM) towards destination choice (DC). Moreover, the study also explores the effects of environmental sustainability (ES) towards satisfaction (ST). Lastly, the study also examines the ST mediated by DC with the final impact on revisit intention (RI). A number of 503 tourists participated in this study and questionnaires were distributed at tourist attraction spots in Langkawi. The data was analysed using SPSS and Structural Equation Modelling in Smart-PLS. The finding indicates that there is a significant relationship between DP, e-WOM, and CM on DC, but not between TM and DC. Moreover, ES also shows a significant relationship with ST, and the finding also indicates that ST mediates the relationship between DC and RI. The research has extended the body of knowledge in EDT, SOR model, as well as consumer behaviour study. There are practical implications to practitioners and the policy makers, as they should emphasise on the factors that could make Langkawi a competitive destination and sustainable in the long term. Practitioners are encouraged to develop a variety of packages which shows that it can encourage tourists to revisit Langkawi in the future. Moreover, marketers can also highlight the personality of Langkawi in their marketing tools as the personality of Langkawi gives an impact on tourist destination choice.